Multiple myeloma and kidney disease - Natalia Zarankiewicz; Katarzyna Kosz; Martyna Zielińska; Klaudia Remjasz; Aleksandra Kuchnicka; Julia Kuchnicka; Klaudia Sapuła; Jakub Aleksandrowicz; Wojciech Siedlecki (Kazimierz Wielki University, 2022)
Abstract   Background: Multiple myeloma is a clonal plasma cell neoplasm which affects 1% of all malignancies. In this article we reviewed epidemiology, symptoms with particular attention to renal failure and its manifestation in multiple myeloma (MM). Material and methods: This paper was based on medical articles collected in PubMed from 2001 to 2022, medical websites and books. The research has been done by looking through key words such as: "multiple myeloma", "myeloma cast nephropathy", "bortezomib", "RANKL" Results: Multiple myeloma has indolent course and many patients present renal disorders at the moment of diagnosis. The use of novel therapies can reverse renal failure. Conclusions: Treatment of the patients with MM and kidney disease is challenging for health care professionals. Doctors have to adjust treatment to provide the best therapeutic effects.